Association between age and outcomes following thrombectomy for anterior circulation emergent large vessel occlusion is determined by degree of recanalisation. (1st June 2018) - Jayaraman, Mahesh V; Kishkovich, Thomas; Baird, Grayson L; Hemendinger, Morgan L; Tung, Eric L; Yaghi, Shadi; Cutting, Shawna; Saad, Ali; Burton, Tina M; Mac Grory, Brian; Haas, Richard A; Furie, Karen L; et al.
Abstract : Background: Older patients undergoing thrombectomy for emergent large vessel occlusion have worse outcomes. However, complete or near-complete reperfusion (modified Thrombolysis in Cerebral Ischemia (mTICI) score of 2 c/3) is associated with improved outcomes compared with partial recanalisation (mTICI 2b). Objective: To examine the relationship between outcomes and age separately for the mTICI 2c/3, 2b and 0-2a groups in patients undergoing thrombectomy for anterior circulation emergent large vessel occlusion. Methods: Retrospective review of 157 consecutive patients undergoing thrombectomy at a single centre with an occlusion of the internal carotid artery (ICA), M1 or proximal M2 segments of the middle cerebral artery (MCA). Angiograms were graded in a blinded fashion. Patients were divided into three groups: mTICI 0-2a, mTICI 2b, and mTICI 2c/3. Demographics and workflow parameters were compared. Outcomes at 90 days were compared as a function of age, using both the conventional modified Rankin scale (mRs) and utility weighted mRs (UWmRs). Results: There were 72, 61 and 24 patients in the mTICI 2c/3, 2b and 0-2a groups, respectively. Outcomes were significantly worse with increasing age for the mTICI 2b group, but not for the mTICI 0-2a and 2c/3 groups (P=0.0002). With increasing age, outcomes of the mTICI 2b group approached those of the mTICI 0-2a group. However, outcomes of the mTICI 2c/3 groups were similar for all ages. This association was present for both the original mRs and UWmRs. Conclusion: Increasing age was associated with worse outcomes for those with partial (mTICI 2b) recanalisation, not in patients with complete (mTICI 2c/3) recanalisation.